Postauthorization safety study of betaine anhydrous. Issue 4 (6th April 2022) - Mütze, Ulrike; Gleich, Florian; Garbade, Sven F.; Plisson, Céline; Aldámiz‐Echevarría, Luis; Arrieta, Francisco; Ballhausen, Diana; Zielonka, Matthias; Petković Ramadža, Danijela; Baumgartner, Matthias R.; Cano, Aline; García Jiménez, María Concepción; et al.
Abstract: Patient registries for rare diseases enable systematic data collection and can also be used to facilitate postauthorization safety studies (PASS) for orphan drugs. This study evaluates the PASS for betaine anhydrous (Cystadane), conducted as public private partnership (PPP) between the European network and registry for homocystinurias and methylation defects and the marketing authorization holder (MAH). Data were prospectively collected, 2013–2016, in a noninterventional, international, multicenter, registry study. Putative adverse and severe adverse events were reported to the MAH's pharmacovigilance. In total, 130 individuals with vitamin B6 nonresponsive ( N = 54) and partially responsive ( N = 7) cystathionine beta‐synthase (CBS) deficiency, as well as 5, 10‐methylenetetrahydrofolate reductase (MTHFR; N = 21) deficiency and cobalamin C ( N = 48) disease were included. Median (range) duration of treatment with betaine anhydrous was 6.8 (0–9.8) years. The prescribed betaine dose exceeded the recommended maximum (6 g/day) in 49% of individuals older than 10 years because of continued dose adaptation to weight; however, with disease‐specific differences (minimum: 31% in B6 nonresponsive CBS deficiency, maximum: 67% in MTHFR deficiency). Despite dose escalation no new or potential risk was identified. Combined disease‐specific treatment decreased mean ± SD total plasma homocysteine concentrations from 203 ± 116 to 81 ± 51 μmol/L ( p < 0.0001), except in MTHFR deficiency. Recommendations for betaine anhydrous dosage were revised for individuals ≥ 10 years. PPPs between MAH and international scientific consortia can be considered a reliable model for implementing a PASS, reutilizing well‐established structures and avoiding data duplication and fragmentation. Abstract :